An Analysis of The Impact of Service Quality on Customer Satisfaction in Malaysian Research Universities (Sains Humanika, 2012)
The purpose of this paper is to present a regression model for predicting international postgraduate students satisfaction based on service quality. Ironically, most studies on student satisfaction tend to concentrate on the undergraduate students and/or the education providers. The university management would benefit by knowing which factors have impact on international students’ satisfaction. A multiple regression analysis was used upon a database 522 international postgraduate students who were selected based on stratified sampling from five research universities. The analysis started with descriptive analysis followed by regression analysis. Five factors in the form of professionalism, reliability, hospitality,tangibles, and commitment were examined as predictors for the students’ satisfaction. After conducting regression analysis, only professionalism and reliability, were found to be valid as independent variables for predicting satisfaction. As the international postgraduate segment is more lucrative, this research is timely and presents significantly different results from those found in the current literature.
Keywords: Postgraduates; higher education; student satisfaction